2007
DOI: 10.1089/aid.2006.0290
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Observation of Adolescents Initiating HAART Therapy: Three-Year Follow-Up

Abstract: The PACTG 381 cohort included 120 adolescents infected via high-risk behaviors and treated with at least two NRTIs plus either a protease inhibitor or an efavirenz-containing HAART regimen. After 24 weeks of therapy, only 69 of 118 (59%) evaluable subjects had undetectable viral loads. We now present findings of the study after 3 years of follow-up. Virologic, immunologic, and treatment information were collected from subjects every 12 weeks beyond the first 24 weeks of therapy through 156 weeks. Of the 120 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 18 publications
4
50
0
1
Order By: Relevance
“…[3][4][5] Data from the REACH Project demonstrated that long-term adherence is a particular challenge for adolescents. 22 We found very high rates of adherence in subjects on our study placed onto SCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Data from the REACH Project demonstrated that long-term adherence is a particular challenge for adolescents. 22 We found very high rates of adherence in subjects on our study placed onto SCT.…”
Section: Discussionmentioning
confidence: 99%
“…2 Research on the impact of highly active antiretroviral therapy (HAART), especially management strategies, is limited in this population. [3][4][5] A number of management strategies have been tried to limit antiretroviral exposure, enhance adherence, limit medication-associated toxicity, and improve quality of life. These strategies include CD4-guided treatment interruptions, structure treatment interruptions, and short-cycle therapy.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Similar findings among adolescents and young adults who acquired HIV horizontally are reported, with as few as 24% in 1 study achieving virologic suppression at 3 years after initiation of cART. 10 Such observations reinforce the need to design, implement, and evaluate strategies to increase and sustain adherence to therapy in this group. Interventions must factor the adolescents' stage of development, education level, health literacy and coping ability, and structural environment.…”
mentioning
confidence: 95%
“…In PENPACT-1, viral failure was worse at age extremes, consistent with studies finding poor viral suppression at younger ages 6,19 and myriad adherence difficulties in adolescents. 7,54 …”
Section: Figurementioning
confidence: 99%